The Influence of Business Management, Success Process, Long Term Plans, Culture, Business Targets, Family Assistance, Decision Making, Knowledge and Skills of Business Owners on the Existence of Family based Business in the Potterial Industry Center of Pulutan Village - Taroreh, Rita Norce; Walangitan, Mac Donald Bertrand; Timbuleng, Maxie; Pinatik, Sherly (Jurnal Ekonomi dan Bisnis Digital, 2025)
The acceleration of industrial and regional growth including the MSME sector is one of the dimensions of the current government's Leading Sector development. Family business is a form of MSME that involves several family members in the ownership or operation of the business. The main problem experienced by family businesses is the problem of professionalism and business succession to their successors for business continuity. A family business takes time and effort to build. One form of MSMEs in Minahasa is the center of the pottery industry in Pulutan Village, Remboken District. The pottery industry has existed in Pulutan since this village was founded until now. The existence of the business continues to be maintained because it is driven by family-based village communities. The results of this study found a link between business management, succession process, availability of long-term plans, culture, business targets, family assistance, decision making, knowledge and skills of business owners on the success of family business succession in the Pulutan Village pottery industry center.